Publisher Correction: An expression atlas of variant ionotropic glutamate receptors identifies a molecular basis of carbonation sensing - Juan Antonio Sánchez-Alcañiz (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.